Cricket Flour and Pullulan Microparticle Formation via Electro-Blow Spinning as a New Method for the Protection of Antioxidant Compounds from Fruit Extracts - Sabina I. Wilkanowicz; Keara T. Saud (Polish Journal of Food and Nutrition Sciences)
Cricket flour was evaluated as an encapsulation material for protecting phenolic-rich fruit extracts (cranberry fruit and pomegranate peel extracts) and compared to pullulan. Electro-blow spinning (EBS) was used as a high throughput technique for encapsulation and compared to freeze-drying. The particles’ morphology was analyzed via scanning electron microscopy (SEM). Fourier transform infrared and UV-vis spectroscopy were used for chemical characterization and encapsulation efficiency determination, respectively. The extract stability and antioxidant activity of the microparticles were studied by exposing samples to UV light irradiation for 30 h. Both extracts were successfully encapsulated in all encapsulating materials. SEM analysis showed that the obtained materials were micro-sized with a shape of capsule. Encapsulation efficiency was between 58.5 and 88.1% for the samples made via EBS and 51.2 to 79.3% for those made via freeze-drying. Encapsulation brought a significant improvement of extract stability and antioxidant activity. The non-protected extracts lost 50% of their antioxidant activity after 30 h of UV light radiation, while those protected with pullulan and cricket flour filtrate mixture experienced a 20% activity reduction. These findings indicate EBS to be a successful technique for the encapsulation of bioactive molecules, and cricket flour to be a new potential encapsulating material candidate that proves best when using a copolymer, such as pullulan.